EVALUASI PELABUHAN TIBAR TIMOR-LESTE DENGAN INDIKATOR HIJAU - Juvinal Rodrigues; Peter F. Kaming; Ambrosius Koesmargono (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2021)
This study aims to find out what indicators are applied in the infrastructure of Tibar Port, port of East Timor and to formulate a port development strategy. The research location is in East Timor, a small country located in the south of East Nusa Tenggara, Indonesia. This research was conducted using the gap between reality and expectations of respondents using the Gap Analysis method. The result showed that the Customer Satisfaction Index in general, was 77, 6% and was in the 68-83 intervals therefore, the Tibar East Timor Partnership was categorized as “Satisfied”. The gap between expectations and reality <1 is already good. The aspect that has the biggest GAP is the Energy and Resources Management Aspect with an Average Gap of 1.0. Whereas the aspects that have the smallest GAP are the Port Ecology Management Aspect and the Science and Technology Aspect Imaging and Social Participation with an Average Gap of 0.8. The indicators that must be considered are those in quadrant I: Noise control (noise pollution), Conservation, and ecological protection (interaction of living things and the environment) of the port, Quality management of clean water sources.